Research Progress on the Preparation and Modification of Cathodic Electrophoretic Coatings - ZHANG Zhe, LIU Lan - xuan, LI Dong - dong, LEI Rui - cheng, LIU Xiu - sheng, WANG Ming - zhao (Cailiao Baohu, 2021)
Cathodic electrophoretic coatings combine the advantages of water - based coatings and electrophoretic coatings, which not only reduce pollution to water sources and the atmosphere, but also have good appearance and flatness of the coating film, and a high degree of automation. Therefore, it has become a hot research direction of coatings research in recent years. According to the different main resins of cathodic electrophoretic coatings, several common cathodic electrophoretic coating systems and their modification research progress were reviewed in this paper. By comparing and analyzing different modification methods, and combining with the current actual needs, the modification ideas and development trends of cathodic electrophoretic coatings were put forward.